1976
DOI: 10.1111/j.1432-1033.1976.tb10773.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Bound Phosphoglucose Isomerase. Formation and Properties of Monomers and Hybrids

Abstract: Dimeric phosphoglucose isomerase from rabbit muscle was immobilized by reaction with cyanogen-bromide-activated Sepharose 4B. The catalytic parameters and stability properties of the free and matrix-bound isomerases were essentially identical. Total monomerisation of the matrix-bound enzyme was achieved with 8 M urea as determined by a study in which one subunit was labelled with i~do['~C]acetate and the other with the 3H-labelled reagent. Although matrixbound monomers were devoid of isomerase activity, they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
(7 reference statements)
5
16
0
Order By: Relevance
“…Applying a symmetry operation can generate the dimer, and this is prerequisite for viewing either active-site region, each of which is comprised of chains from both monomers. This arrangement agrees with biochemical data showing that the dimer is required for enzymatic activity 7 but is at odds with data suggesting that AMF exhibits PGI enzyme activity and yet appears to exist as a monomer. 3 As expected, the structure of porcine PGI is highly similar to those of PGIs from other mammalian sources.…”
supporting
confidence: 84%
“…Applying a symmetry operation can generate the dimer, and this is prerequisite for viewing either active-site region, each of which is comprised of chains from both monomers. This arrangement agrees with biochemical data showing that the dimer is required for enzymatic activity 7 but is at odds with data suggesting that AMF exhibits PGI enzyme activity and yet appears to exist as a monomer. 3 As expected, the structure of porcine PGI is highly similar to those of PGIs from other mammalian sources.…”
supporting
confidence: 84%
“…Hybridization experiments on a solid phase might provide important information about subunit interactions in oligomeric proteins, as demonstrated here and in other studies [6,38]. An inherent advantage in the solid-phase approach is that the desired hybrid is obtained directly without the need for any separation steps.…”
Section: Discussionmentioning
confidence: 69%
“…(EE)cm denotes carboxymethylated dimeric EE; other details are the same as in Table 2 Preparation Activity immobilized subunits but also that matrix-bound S subunits are not inactivated due to the immobilizationper se. A similar approach to check that covalently bound inactive subunits are in fact active upon reassociation with soluble subunits was used in studies of matrix-bound glycogen phosphorylase monomers [4] and immobilized phosphoglucose isomerase subunits [6]. However, in these studies enzyme activity was restored on addition of soluble subunits which were previously inactivated by modification-in their active sites.…”
Section: Regeneration Of Enzyme Activity Of Immobilized Urea-treated mentioning
confidence: 99%
“…Acid-dependent sequestration of PGI/AMF PGI/AMF is an oligomeric protein whose enzymatic function is dependent on dimer formation (Bruch et al, 1976) and acidification to pH 5 is associated with loss of enzymatic activity due to disruption of PGI/AMF oligomeric structure (Amraei et al, 2003;Dyson and Noltmann, 1968). We have previously shown that the acid-induced association of PGI/AMF with FN is associated with both changes in the tertiary structure of the protein and disruption of the oligomeric structure of the protein (Amraei et al, 2003).…”
Section: Discussionmentioning
confidence: 99%